Distinct Endothelial Cell Responses in the Heart and Kidney Microvasculature Characterize the Progression of Heart Failure With Preserved Ejection Fraction in the Obese ZSF1 Rat With Cardiorenal Metabolic Syndrome. (April 2016) - van Dijk, Christian G.M.; Oosterhuis, Nynke R.; Xu, Yan Juan; Brandt, Maarten; Paulus, Walter J.; van Heerebeek, Loek; Duncker, Dirk J.; Verhaar, Marianne C.; Fontoura, Dulce; Lourenço, André P.; Leite-Moreira, Adelino F.; Falcão-Pires, Inês; et al.
Abstract : Background—: The combination of cardiac and renal disease driven by metabolic risk factors, referred to as cardiorenal metabolic syndrome (CRMS), is increasingly recognized as a critical pathological entity. The contribution of (micro)vascular injury to CRMS is considered to be substantial. However, mechanistic studies are hampered by lack of in vivo models that mimic the natural onset of the disease. Here, we evaluated the coronary and renal microvasculature during CRMS development in obese diabetic Zucker fatty/Spontaneously hypertensive heart failure F1 hybrid (ZSF1) rats. Methods and Results—: Echocardiographic, urine, and blood evaluations were conducted in 3 groups (Wistar-Kyoto, lean ZSF1, and obese ZSF1) at 20 and 25 weeks of age. Immunohistological evaluation of renal and cardiac tissues was conducted at both time points. At 20 and 25 weeks, obese ZSF1 rats showed higher body weight, significant left ventricular hypertrophy, and impaired diastolic function compared with all other groups. Indices of systolic function did not differ between groups. Obese ZSF1 rats developed hyperproliferative vascular foci in the subendocardium, which lacked microvascular organization and were predilection sites of inflammation and fibrosis. In the kidney, obese ZSF1 animals showed regression of the peritubular and glomerular microvasculature, accompanied by tubulointerstitial damage, glomerulosclerosis, and proteinuria. Conclusions—: The obese ZSF1 rat strain is a suitable in vivo model for CRMS, sharing characteristics with the human syndrome during the earliest onset of disease. In these rats, CRMS induces microvascular fibrotic responses in heart and kidneys, associated with functional impairment of both organs. Abstract : Supplemental Digital Content is available in the text.